1993
DOI: 10.1111/j.1550-7408.1993.tb04478.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of an Opioid Receptor in the Ciliate Tetrahymena

Abstract: A pharmacological characterization has been performed of the opioid receptor involved in modulation of phagocytosis in the protozoan ciliate Tetrahymena. Studies on inhibition of phagocytosis by mammalian prototypic opioid agonists revealed that morphine and beta-endorphin have the highest intrinsic activity, whereas all the other opioids tested can only be considered partial agonists. However, morphine (a mu-receptor agonist) is twice as potent as beta-endorphin (a delta-receptor agonist). Furthermore, the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Wu et al (1997) [16] demonstrated that the drug was ineffective to inhibit the immobilizing effect-induced by an opioid in the organism. Josefsson and Johansson (1979) [17] demonstrated a naloxone-reversible opioid effect on pinocytosis in Amoeba, and similar observation was made by Chiesa et al (1993) [18], as well as by Salaman et al (1990) [19], who studied phagocytosis in Tetrahymena. In contrast to these data, we studied the opioid receptor-ligand relation in accumulation or avoidance of Paramecium.…”
Section: Discussionmentioning
confidence: 54%
“…Wu et al (1997) [16] demonstrated that the drug was ineffective to inhibit the immobilizing effect-induced by an opioid in the organism. Josefsson and Johansson (1979) [17] demonstrated a naloxone-reversible opioid effect on pinocytosis in Amoeba, and similar observation was made by Chiesa et al (1993) [18], as well as by Salaman et al (1990) [19], who studied phagocytosis in Tetrahymena. In contrast to these data, we studied the opioid receptor-ligand relation in accumulation or avoidance of Paramecium.…”
Section: Discussionmentioning
confidence: 54%
“…Tetrahymena opioids inhibit phagocytosis of Tetrahymena by a naloxonereversible mechanism [45]. The opioid receptors of Tetrahymena are more sensitive to beta-endorphin and most sensitive to morphine [46], which points to the mu-likeness in some pharmacological characters. Chronic treatment with an opioid causes tolerance [47].…”
Section: Peptide Hormonesmentioning
confidence: 99%
“…Unicellulars synthesize, store, and secrete amino acid-and polypeptide-type hormones characteristic to multicellular animals (mammals) [4][5][6][7][8][9][10][11][12][13][14]. In addition, the cells have mammalian receptor-like structures in the plasma membrane, which bind these hormones and the cells react to them [15][16][17][18][19], as they have signal transducer pathways [20][21][22][23]. Many cell functions of the unicellular ciliate Tetrahymena are influenced by the hormones and their effect sometimes seems to be specific [19].…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Some of these hormones have receptors which are similar to the mammalian ones [7][8][9][10][11][12] and the reaction of Tetrahymena provoked by the hormones is also similar to the reaction of mammalian cells. For example: insulin has such receptors [7][8][9] and after binding, the signal transduction is similar to the mammalian one.…”
Section: Introductionmentioning
confidence: 99%